ECONOMETRIC ASSESSMENT OF IMPACT OF ARTIFICIAL INTELLIGENCE ON HUMAN CAPITAL AND LABOR MARKET (Scientific electronic journal "Labor Economics and Human Capital", 2023)
In this article, the impact of artificial intelligence technologies on the development of the country's human capital and changes in the labor market is analyzed empirically and econometrically. The research was carried out on the basis of the sociological research method, and the questionnaire was prepared on the basis of the Likert scale. The validity and reliability of the survey options based on the Likert scale is based on the evaluation of its internal consistency. "Cronbach's alpha" coefficient was used to evaluate the internal consistency and reliability of internal consistency of the questionnaire using the IBM SPSS Statistics 22.0 program. As a result of the study, the result of testing the hypothesis that human capital has a positive effect on the state of digital development as a result of the impact of artificial intelligence on the labor market shows that there is a strong relationship between them. It has become clear that the impact of artificial intelligence on the education system can also directly affect the digital development of human capital in the country. It also became known that the healthcare system under the influence of artificial intelligence will have a positive effect on the digital development of human capital.
Keywords: artificial intelligence, digital development of human capital, labor market transformation